2021
DOI: 10.3390/jcm10153375
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Diabetes Mellitus on Cervical Spine Surgery for Ossification of the Posterior Longitudinal Ligament

Abstract: Ossification of the posterior longitudinal ligament (OPLL) is commonly associated with diabetes mellitus (DM); however, the impact of DM on cervical spine surgery for OPLL remains unclear. This study was performed to evaluate the influence of diabetes DM on the outcomes following cervical spine surgery for OPLL. In total, 478 patients with cervical OPLL who underwent surgical treatment were prospectively recruited from April 2015 to July 2017. Functional measurements were conducted at baseline and at 6 months,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The similarity of the cohorts used in 10 of the included studies were deemed unclear ( 32 , 35 , 36 , 49 , 52 , 56 , 58 , 60 , 61 , 86 ), mainly due to a lack of clear selection criteria. Measurement of exposures was mostly adequate, except in five studies ( 36 , 47 , 49 , 52 , 66 ), where the reporting of how exposures were measured were not deemed to be detailed enough. Similarly, seven studies did not include sufficient detail to be able to confidently conclude that exposures were measured in a valid and reliable manner ( 37 , 47 , 49 , 52 , 53 , 55 , 66 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The similarity of the cohorts used in 10 of the included studies were deemed unclear ( 32 , 35 , 36 , 49 , 52 , 56 , 58 , 60 , 61 , 86 ), mainly due to a lack of clear selection criteria. Measurement of exposures was mostly adequate, except in five studies ( 36 , 47 , 49 , 52 , 66 ), where the reporting of how exposures were measured were not deemed to be detailed enough. Similarly, seven studies did not include sufficient detail to be able to confidently conclude that exposures were measured in a valid and reliable manner ( 37 , 47 , 49 , 52 , 53 , 55 , 66 ).…”
Section: Resultsmentioning
confidence: 99%
“…Measurement of exposures was mostly adequate, except in five studies ( 36 , 47 , 49 , 52 , 66 ), where the reporting of how exposures were measured were not deemed to be detailed enough. Similarly, seven studies did not include sufficient detail to be able to confidently conclude that exposures were measured in a valid and reliable manner ( 37 , 47 , 49 , 52 , 53 , 55 , 66 ). Identification of confounding factors (e.g., sex, age and duration of symptoms) was mostly adequate, except in six studies that appeared to miss key confounders ( 47 , 52 , 56 , 58 , 60 , 61 ), most commonly due to lack of complete exclusion criteria, and two studies that appeared to be missing most confounders ( 32 , 49 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk factors for postoperative upper airway complications include blood loss >300 mL, surgery on 4 or more vertebral bodies, including C4, and operation time >5 hours 40,41 . Incidences of hoarseness reportedly range from 0% to 13.7% for entire anterior approach surgeries and 0.3%–4.6% specifically for OPLL surgeries 15,42–44 . Surgical interventions involving C2/3 and C3/4 segments, along with prolonged operation times, increase the likelihood of postoperative hoarseness 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with mild symptoms can be treated conservatively, but patients with progressive myelopathy frequently require surgical intervention. 2 Previous research has reported that age, 3 preoperative neurological score, 4 comorbidities, 5 surgical approach, 6,7 high signal intensity on magnetic resonance imaging, 8,9 and other factors are associated with surgical outcomes for the treatment of cervical OPLL. 10 However, the effect of symptom duration on postoperative outcomes for cervical OPLL and the threshold of symptom duration for favorable recovery have not been adequately studied.…”
mentioning
confidence: 99%